INFLUENCE TUITION FEES AND FACILITIES ON STUDENT DECISIONS FOR CHOOSE STUDY AT THE FACULTY OF AGRO TECHNOLOGY, UNIVERSITAS PRIMA INDONESIA - Salman Faris; Ahmad Irhan Sitompul; Tuty Nainggolan (Jurnal Ekonomi, 2023)
This study aims to determine the effect of tuition fees and facilities on student decisions to choose to study at the Faculty of Agro Technology, Prima Indonesia University partially or simultaneously. The research was conducted on students of the Faculty of Agro Technology UNPRI. The population in the study were students of the Faculty of Agro Technology UNPRI. The data collection method in this study is a questionnaire or questionnaire. The sampling technique used is the Random Sampling technique. Determining the number of samples in this study used the Slovin formula with an error rate of 5% so that a total sample of 121 students was obtained from a total population of 173 students from the Faculty of Agro Technology UNPRI. Test prerequisite analysis using validity, and reliability tests. Data analysis techniques used descriptive analysis, multiple correlation analysis, multiple regression analysis, and the coefficient of determination using SPSS version 20.0. The results of research originating from data processing show a positive relationship between the variables of education costs and facilities on the decision to choose students of the Faculty of Agro Technology UNPRI. Partially, the effect of education costs and facilities on the performance of UNPRI permanent lecturers is 0.129 each; and 0.144. Simultaneously, the variable costs of education and facilities have a significant influence on the decision to choose students from the Faculty of Agro Technology, UNPRI, which is 0.273. From the results of the analysis, it was found that part of the influence of competence, training, and motivation on the performance of UNPRI permanent lecturers was 12.9% and 14.4%, respectively. Simultaneously the effect of competence, training, and motivation on the performance of UNPRI permanent lecturers is 27.30% and the rest is influenced by other variables not proposed in this study.